Prosocial priming and bystander effect in an online context - Scaffidi Abbate, Costanza; Misuraca, Raffaella; Vaccaro, Chiara; Roccella, Michele; Vetri, Luigi; Miceli, Silvana (Frontiers in Psychology, 2022)
The present study examined the influence of priming the concept of prosociality on the bystander effect in a virtual context. Participants were sent an email message requesting a plea for help and were randomly assigned to one of four conditions in a 2 (Bystander: 0 vs. 14) x 2 (Priming: present vs. absent) design. The results demonstrated support for the study hypothesis. As expected, the virtual presence of many others significantly reduced email responsiveness except when the request for help is preceded by prosocial priming. Implications of these findings for the literature on the bystander effect and priming are discussed.